2011
DOI: 10.1073/pnas.1010689108
|View full text |Cite
|
Sign up to set email alerts
|

Structure of betaglycan zona pellucida (ZP)-C domain provides insights into ZP-mediated protein polymerization and TGF-β binding

Abstract: The zona pellucida (ZP) domain is a bipartite protein structural element comprised of ZP-N and ZP-C regions. Most notable for its ability to mediate protein polymerization, many ZP proteins polymerize and assemble into long fibrils that form specialized extracellular matrices. Other ZP proteins (namely, betaglycan and endoglin) do not polymerize but serve as important membrane coreceptors for ligands in the transforming growth factor-β (TGF-β) superfamily. Here, we present the 2.0-Å resolution crystal structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
77
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 46 publications
8
77
0
Order By: Relevance
“…S3 and S8). Remarkably, these combinations coincide with the different polymerization abilities of the corresponding proteins: BG and ENG do not polymerize; ZP1-ZP4 and TECTB heteropolymerize; and UMOD, GP2, and TECTA homopolymerize (7,17,37,38). This observation is consistent with the idea that in the last set of proteins, coupling of an α1/β1-containing linker to ZP-C induces an extended conformation of the ZP module.…”
Section: The Crystal Structure Of Zp2 Zp-c Reveals That Zp Modules Hasupporting
confidence: 77%
See 3 more Smart Citations
“…S3 and S8). Remarkably, these combinations coincide with the different polymerization abilities of the corresponding proteins: BG and ENG do not polymerize; ZP1-ZP4 and TECTB heteropolymerize; and UMOD, GP2, and TECTA homopolymerize (7,17,37,38). This observation is consistent with the idea that in the last set of proteins, coupling of an α1/β1-containing linker to ZP-C induces an extended conformation of the ZP module.…”
Section: The Crystal Structure Of Zp2 Zp-c Reveals That Zp Modules Hasupporting
confidence: 77%
“…Surprisingly, our crystallographic data reveal that UMOD ZP-C (Figs. S1D and S5A) also shares the same fold and disulfide connectivity of ZP3 and BG ZP-Cs (3,16,17) (Fig. S5 B and C), except for the C a -C b disulfide not found in ZP3 proteins (15) (Fig.…”
Section: E)mentioning
confidence: 99%
See 2 more Smart Citations
“…Porcine ZP3 and ZP4 exhibit disulfi de patterns different from the ZP3 and ZP1/ZP2/ZP4 patterns reported for mice, rats, humans, and fi sh (Kanai et al 2008 ). The chick homologue of the mammalian ZP3 precursor protein has a pig-type ZP3 pattern (Han et al 2010 ), whereas betaglycan has a pig-type ZP1/ZP2/ZP4 pattern (Lin et al 2011 ), as revealed by X-ray crystallography. The two ZP3 disulfi de bond pattern s cause only subtle structural differences (Han et al 2010 ).…”
Section: Polypeptides Of Porcine and Bovine Zpgsmentioning
confidence: 99%